2016
DOI: 10.3109/09513590.2016.1163673
|View full text |Cite
|
Sign up to set email alerts
|

Kruppel-like factor 4 (KLF-4) inhibits the epithelial-to-mesenchymal transition and proliferation of human endometrial carcinoma cells

Abstract: Kruppel-like factors (KLFs) are a group of transcriptional regulators, being tumor-suppressive in various types of cancers, but not clear in human endometrial carcinoma (EC). We investigated the KLF-4 expression in both mRNA and protein levels in 29 EC specimens with RT-qPCR and Western blotting methods, and then to determine its promotion to Epithelial-to-mesenchymal transition (EMT) and proliferation of EC Ishikawa cells, via analyzing EMT-associated markers and via CCK-8 and colony forming assay. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This phosphorylation induced nuclear entry was found to be critical for E47 to promote EMT and colon cancer metastasis (113). Krüppel-like factor family of Transcription Factors: Krüppel-like factor 4 (KLF4) has been shown to act as a negative regulator of EMT or even inducer of MET in a wide variety of cell/tissue types by different laboratories (114)(115)(116)(117)(118)(119)(120)(121)(122)(123). In fact, KLF4 expression was found to be downregulated in cells undergoing EMT in presence of TGFβ.…”
Section: Bhlh Family Transcription Factors: Twist Family Proteinsmentioning
confidence: 99%
“…This phosphorylation induced nuclear entry was found to be critical for E47 to promote EMT and colon cancer metastasis (113). Krüppel-like factor family of Transcription Factors: Krüppel-like factor 4 (KLF4) has been shown to act as a negative regulator of EMT or even inducer of MET in a wide variety of cell/tissue types by different laboratories (114)(115)(116)(117)(118)(119)(120)(121)(122)(123). In fact, KLF4 expression was found to be downregulated in cells undergoing EMT in presence of TGFβ.…”
Section: Bhlh Family Transcription Factors: Twist Family Proteinsmentioning
confidence: 99%
“…EndoMT is required for ECC development, and KLF4 has been shown to inhibit or activate EndoMT 22,[40][41][42][43] . To decouple KLF4's role in EndoMT, we examined the expression patterns of Vimentin (Vim, mesenchymal marker) and Kinase Insert Domain Receptor (Kdr, endothelial marker) to test whether KLF4-low cells in the center of the AVC were more or less likely to undergo EndoMT.…”
Section: Klf4 Expression Negatively Correlates With Cushion Endomt Pr...mentioning
confidence: 99%
“…klf2 -/or klf5 -/mice die in utero during embryonic life (29,30). Previous studies have revealed that KLFs participate in proliferation, apoptosis, epithelial-mesenchymal transition (EMT), angiogenesis and other malignant biological behavior of cancer (14,(31)(32)(33). KLF4 inhibits EMT and proliferation of endometrial cancer cells, whilst KLF8 promotes EMT and proliferation of bladder cancer cells (34,35); these findings suggest that the KLF gene family may serve a critical role in cancer genesis and prognosis.…”
Section: Bioinformatics Analysis Of Klf2 As a Potential Prognostic Fa...mentioning
confidence: 99%